AD, Volume 28, n° 3 & 4, 2003 - Full Issue - Journal System (Africa Development, 2003)
Contents Globalisation and Social Security in Low-Income Countries: The Case of Côte d'Ivoire Steven D'Haeseleer & Jos Berghman ...................1 Institutionalised Marginality, Social Conflicts and the Quest for National Unity in an African Nation-State: A Theoretical Exploration Philip Ogo Ujomu .................................22 Globalisation and Industrial Performance in Nigeria Ifeanyi Onyeonoru .................................36 Gender, Globalisation and Marginalisation in Africa Lai Olurode ..............................................67 The Nature and Scope of Production Sub-contracting in Nigeria Dickson Dare Ajayi ...................................89 Globalisation, Institutional Arrangemen Poverty in Rural Cameroon Francis Menjo Baye ...................................112 Les immigrés nigérians à Douala: problèmes et stratégies d'insertion sociale des étrangers en milieu urbain Biaise-Jacques Nkene ..................................142 An Empirical Profile of Weak States in Sub-Saharan Africa J. Atiku-Abubakar & Yoku Shaw-Taylor ..............168 Secondary Education - A 'Tool' for National Development in Ghana. A Critical Appraisal of the Post-Colonial Context Hubert O. Quist ..............................186 The Challenges of Education and Development in Post-Colonial Kenya Mwenda Ntarangwi ..............................211